Matemática, História e Compreensão - Fossa, John Andrew (Revista Cocar, 2012)
Investiga-se três maneiras em que a História da Matemática pode ser utilizada como um instrumento pedagógico. Em primeiro lugar, a história tem sido tradicionalmente encarada como um apoio à motivação do aluno. Vistas as limitações dessa abordagem, considera-se duas possibilidades mais eficazes. A primeira é o uso da História da Matemática como um agente de formação cultural, em que a história aborda a matemática como parte do patrimônio cultural da humanidade. A segunda é o uso da História da Matemática como um agente de formação cognitiva na sala de aula. Nesse sentido, investiga-se as vantagens de utilizar a história para elaborar atividades construtivistas. This study presents the results of a research developed with 30 students of a 8th grade class of the fundamental teaching of a public school from the municipallity of Oeiras do Pará (PA), in lhe year of 2005. This research aim was to investigate the feasibility of the teaching of flat figures areas using activities of rediscovery. To carry it out it was applied a pre-test containing problems which involved the area calculation. After the resuits found in the pre-test., eight activities based on the technic of the rediscovery were elaborated and applied in the classroom. At the end of these activities, it was applied a post-test to the investigated individuals containing the same questions of the pre-test. The achieved results point that, after carrying out the activities developed with the students, there was a significative percentual of right answers referring to the proposed problems, demonstrating that many of the presented difficulties in the pre-test were overcome, giving place to the comprehension and learning of the concepts developeded in this research. This study presents the results of a research developed with 30 students of a 8th grade class of the fundamental teaching of a public school from the municipallity of Oeiras do Pará (PA), in lhe year of 2005. This research aim was to investigate the feasibility of the teaching of flat figures areas using activities of rediscovery. To carry it out it was applied a pre-test containing problems which involved the area calculation. After the resuits found in the pre-test., eight activities based on the technic of the rediscovery were elaborated and applied in the classroom. At the end of these activities, it was applied a post-test to the investigated individuals containing the same questions of the pre-test. The achieved results point that, after carrying out the activities developed with the students, there was a significative percentual of right answers referring to the proposed problems, demonstrating that many of the presented difficulties in the pre-test were overcome, giving place to the comprehension and learning of the concepts developeded in this research. Palavras-Chave: História da Matemática como recurso pedagógico. Matemática e cultura. His-tória e compreensão cognitiva. Mathematics, history and comprehension One investigates three ways in which the History of Mathematics can be used as an educational resource. First of all, history has been traditio-nally seen as a way to motivate students. Given the limitations of this approach, one considers two other, more effective, possibilities. The first is the use of the History of Mathematics as an agent of cultural education, in which history deals with mathematics as a part of mankindâ€™s cultural patrimony. The second is the use of the History of Mathematics as an agent of cognition in the classroom. In this regard, one investigates the advantages of using history in the elaboration of constructivist activities. Key-words: History of Mathematics as an educational resource. Mathematics and Culture. History and Cognition.